Could Treating Atrial Fibrillation Reduce the Risk of Cognitive Decline and Dementia? (Ictus, 2023)
Letter to the Editor on "Could Treating Atrial Fibrillation Reduce the Risk of Cognitive Decline and Dementia?" presented in Volume 4 Issue 1 of 2023 of ICTUS.
Keywords: Dementia; Anticoagulation; cognitive impairment; Atrial Fibrillation